2012
DOI: 10.4172/2155-6156.s2-007
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Effects of Bromocriptine Treatment on Glucose Homeostasis during Hyperglycemic versus Euglycemic Clamp Conditions in Insulin Resistant Hamsters: Bromocriptine as a Unique Postprandial Insulin Sensitizer

Abstract: Background: Postprandial glucose metabolism is deranged in insulin resistant states typified by increased hepatic glucose output and reduced peripheral and hepatic glucose deposition despite elevated plasma insulin levels. And, mounting evidence suggests that postprandial hyperglycemia may potentiate cardiovascular disease. Time-of-day pulsed bromocriptine (a dopamine D2 receptor agonist) administration to insulin resistant animals and humans improves impaired glucose tolerance and post-meal hyperglycemia with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(44 reference statements)
4
11
0
Order By: Relevance
“…Relative to placebo, bromocriptine-QR therapy resulted in a significant decrease from baseline in postprandial glucose after each meal of the day without altering plasma insulin levels (37 mg/dl average decline of postprandial glucose of all three meals, P < 0.002; Figure 8). Given that the drug is substantially cleared from the circulation by lunch time, yet postprandial effects are observed at lunch and dinner, these results (and those described above in insulin-resistant, nondiabetes subjects) support preclinical data concluding a 'resetting' of hypothalamic nutrient-sensing responsiveness to a meal to improve postprandial insulin sensitivity with this therapy [125].…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmensupporting
confidence: 74%
See 1 more Smart Citation
“…Relative to placebo, bromocriptine-QR therapy resulted in a significant decrease from baseline in postprandial glucose after each meal of the day without altering plasma insulin levels (37 mg/dl average decline of postprandial glucose of all three meals, P < 0.002; Figure 8). Given that the drug is substantially cleared from the circulation by lunch time, yet postprandial effects are observed at lunch and dinner, these results (and those described above in insulin-resistant, nondiabetes subjects) support preclinical data concluding a 'resetting' of hypothalamic nutrient-sensing responsiveness to a meal to improve postprandial insulin sensitivity with this therapy [125].…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmensupporting
confidence: 74%
“…Moreover, numerous studies have consistently demonstrated the ability of such circadian-timed daily administration of bromocriptine (systemic or intracerebroventricular) to markedly reduce insulin resistance (particularly during the postprandial state [125,126], in agreement with its ability to improve VMH hypothalamic fuel-sensing mechanisms as described above), hyperinsulinemia and/or glucose intolerance without raising the plasma insulin level, in a variety of animal models of IRS including seasonal insulin-resistant hamsters, SHRs, high-fat fed rats, genetically leptin-deficient ob/ob mice, fattened pigs, and high-fat fed dogs [86,124,[126][127][128][129][130][131][132]. As a composite, these animal studies provide evidence that timed bromocriptine treatment improves dysglycemia by improving (postprandial) insulin action in the liver and/or peripheral insulin-sensitive tissues (e.g.…”
Section: Non-scn Cns Dopaminergic Activities Regulating Peripheral Mementioning
confidence: 99%
“…Interestingly, this B-QR effect on postprandial hyperglycemia is expressed at meal times across the day [22,23] and well after (e.g. 24 h later) the short pulsed duration of bromocriptine into the circulation following its circadian-timed morning administration [37,38], which supports the preclinical data suggesting a 'resetting' of aberrant neuroendocrine responsiveness to mealtime feeding to improve postprandial insulin sensitivity with this therapy [27][28][29][30][31][32][33][34][35][36]. Mechanistic insights into this metabolic phenomenon can be gained from a series of neurophysiological studies that established a facilitatory role for the circadian peak in dopaminergic input activity to the body pacemaker clock system (suprachiasmatic nuclei [SCN]) in the maintenance of normal insulin sensitivity and glucose tolerance in animal models of insulin resistance [26][27][28][29][30][31][32][33][34] described as follows.…”
Section: Discussionmentioning
confidence: 61%
“…The preponderance of available evidence from preclinical and clinical mechanistic studies indicates that a majority (but not the total) of the improvement in glycemic control observed with B-QR therapy in T2DM subjects results from a drug-induced improvement in postprandial glucose metabolism and hyperglycemia [21][22][23][35][36][37][38][39]. Interestingly, this B-QR effect on postprandial hyperglycemia is expressed at meal times across the day [22,23] and well after (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation